2022
DOI: 10.1186/s12877-022-02756-7
|View full text |Cite
|
Sign up to set email alerts
|

A non-interventional cross-sectional re-contact study investigating the relationship between overactive bladder and frailty in older adults in Japan

Abstract: Background Increasing age is associated with frailty and a higher prevalence of overactive bladder (OAB). Given the rapidly increasing proportion of older adults in Japan, a better understanding of the relationship between frailty and OAB is needed to inform future healthcare planning. This study assessed the association between frailty and OAB in older adults in Japan and evaluated the impact on their health-related quality of life (HRQoL). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…There are differing opinions among researchers regarding the relationship between frailty and OAB. In previous studies, Yoshida et al found a positive association between frailty and the occurrence of OAB in older individuals [ 5 ]. Out of 2,953 participants (65% men) aged 65 years or older, 150 (5.1%) had frail OAB, 416 (14.1%) had non-frail OAB, 287 (9.7%) had frail non-OAB, and 2,100 (71.1%) had non-frail non-OAB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are differing opinions among researchers regarding the relationship between frailty and OAB. In previous studies, Yoshida et al found a positive association between frailty and the occurrence of OAB in older individuals [ 5 ]. Out of 2,953 participants (65% men) aged 65 years or older, 150 (5.1%) had frail OAB, 416 (14.1%) had non-frail OAB, 287 (9.7%) had frail non-OAB, and 2,100 (71.1%) had non-frail non-OAB.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a clinical condition associated with aging, characterized by muscle weakness and heightened susceptibility to internal and external stressors [ 3 , 4 ]. In the field of geriatric medicine, specifically urology, and gynecology, conditions such as overactive bladder (OAB) [ 5 ] and genitourinary syndrome of menopause (GSM) have been identified as having detrimental effects on the quality of life for older patients [ 6 , 7 ]. Similar to frailty, OAB and GSM stem from hormonal changes that lead to tissue frailty and significantly impact overall well-being [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…† In this study, benign prostatic hyperplasia, overactive bladder, neurogenic bladder, and stress urinary incontinence, which are representative diseases associated with LUTS, were classified as LUTS-related diseases. ‡ Others: hematuria (20), renal cyst (12), high PSA (8), cystocele (7), chronic prostatitis (7), hydronephrosis (4), renal angiomyolipoma (4), adrenal tumor (3), spermatocele (3), lower abdominal pain (3), urethral caruncle (2), retroperitoneal tumor (1), hematospermia (1), complete phimosis (1), erectile dysfunction (1), chronic renal failure (1), rectovesical fistula (1), skin erosion (1), spermatic cord sarcoidosis (1), scrotal subcutaneous hematoma (1). § Fisher's exact test.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prevalence of frailty associated with urological diseases in Japan has been reported only rarely. The prevalence of frailty assessed by the KCL for patients with overactive bladder (OAB) was 34.3% 12 . However, there are few reports that have examined the various urological diseases associated with a high prevalence of frailty the same criteria.…”
Section: Introductionmentioning
confidence: 99%